Reductions in anxiety and depression symptoms in a subset of outpatients with problematic substance use who received ketamine-assisted psychotherapy: a two-year retrospective chart review - Whinkin, Emily; Eparwa, Therry Rose J.; Julseth, Michelle C.; Schneider, Andrea; Aggarwal, Sunil K. (Frontiers in Psychiatry, 2023)
Objective: Assess changes in symptoms of depression, anxiety, and psychospiritual distress before and after ketamine-assisted psychotherapy in individuals with substance use disorders. Methods: This prospective outcomes study utilized de-identified patient data from the AIMS Medical Outcomes Study (AMOS) and the AIMS Cancer Outcomes Study (ACOS) to evaluate the association between receiving ketamine-assisted psychotherapy (KAP) and psychometric scores in a patient population seen in a community-based urban integrative clinic with past or present substance use disorders as defined by the DSM-V. Validated metrics utilized were Generalized Anxiety Disorder-7 (GAD-7), Patient Health Questionnaire-9 (PHQ-9), and the National Institute of Health - Healing Experiences of All Life Stressors (NIH-HEALS) questionnaires. Results: There were 307 patients identified who received at least one KAP session between November 1, 2020 and October 31, 2022. After applying exclusions, a total of 291 charts were reviewed and 230 AMOS and ACOS consents were confirmed. There were 30 patients identified to have active or previous SUD. A total of 18 patients completed at least one KAP session and at least one baseline and post-KAP metric questionnaire. Average decreases to GAD-7 scores (6.71, n=14) and PHQ-9 scores (7.19, n=16) demonstrate statistically significant improvements in anxiety and depression symptoms after at least one ketamine-assisted psychotherapy session. The average NIH-HEALS score increased though not by a statistically significant amount (5.13, n=15) and, for 33.3% of respondents (n=5), NIH-HEALS scores decreased following ketamine-assisted psychotherapy. Conclusion: Undergoing one to six ketamine-assisted psychotherapy (KAP) sessions in an urban integrative clinic was associated with clinically and statistically significant improvements in anxiety and depression symptoms among individuals with substance use disorders. Changes in psycho-social-spiritual well-being, as measured by NIH-HEALS, showed slight improvement on average. However, NIH-HEALS results were mixed, possibly due to the context of the COVID-19 pandemic or as a result of KAP shifting psycho-spiritual beliefs and experiences.